S'adapter au changement climatique. Analyse critique des nouvelles politiques de gestion de l'environnement. Cas spécifiques de l'agriculture en Inde et du tourisme hivernal en Suisse - Dupuis, Johann (Editions Alphil Presses universitaires suisses, 2015)
Climate change has become a real problem in our time. This book examines the issue of how public policies can adapt to climate change. The study of two very specific cases, situated at opposing points of the world - India and Switzerland - illustrate this question.